ISLAMIC EDUCATION MATERIAL WITH A SOCIOLOGICAL APPROACH - Ishomuddin; Ciptadi, Muhammad Teguh; Haris, Abdul (IMTIYAZ: Jurnal Ilmu Keislaman, 2023)
The sociological approach to Islamic Religious Education Material (PAI) is important and relevant in an increasingly complex and diverse society. The background to this approach can be found in the social challenges faced by modern society, including religious pluralism, interreligious conflict, and rapid social change. In this condition, Islamic religious education needs to align the understanding of religion with the understanding of social realities that influence and are influenced by religion. This study examines the sociological approach in PAI material to create students who deeply understand Islam in a social context. This includes understanding how Islamic teachings influence social structures, norms, values, and social interactions. Another goal is to promote tolerance, interfaith harmony, and critical thinking skills in students. The method used in this study is the literature review method with a qualitative approach. The sociological approach in PAI material concludes that this approach provides a solid foundation for students to integrate religious and deep social understanding. This helps students become individuals of noble character, tolerance, and positive contribution in an increasingly diverse society. Thus, the sociological approach to PAI is important in preparing a generation capable of facing and overcoming social and religious challenges in modern society.